Chapter 2 'Sex and History' Talking Sex with Objects from the Past - Fisher, Kate (Springer Nature, 2016)
The project responds to issues identified by the health and education sector in the UK and internationally, particularly relating to the widely attested difficulty for teachers of opening up conversations around important topics such as consent and pornography.